Upaya Mencegah Tindakan Kekerasan Remaja dengan Peringatan Bahaya Narkoba dan Perundungan dalam Proyek Penguatan Profil Pelajar Pancasila di SMAN 1 Cinangka - Ana Utami Fatoni; Rina Andriani; Umalihayati Umalihayati; Fera Hanifatunnufus; Qoyimah Qoyimah; Deni Herdiyansah; Mutiara Anisa Titian Trisna (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
The writing focused on supporting school program for Kurikulum Merdeka by providing an event namely Proyek Penguatan Profil Pelajar Pancasila (P5) on warning the students for drugs and bullying as parts of juvenile delinquency. The writers highlighted on how to prevent the acts and the impact might come. A live workshop including presentation, discussion, problem-solving, and role-play was held to engange students more involved. The participants were 202 students in the 11th graders, 7 representative teachers, and 2 counseling teachers.